OFFLOADING DECISION SELECTION METHOD FOR ENERGY EFFICIENCY AND LOW LATENCY IN HETEROGENE SIMUATION ENVIRONMENTS - Achmadaniar Anindya Rhosady; Raditya Anggoro (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2022)
Mobile Cloud Computing (MCC) is a technology that can overcome the problems of high computing and limited resources owned by mobile devices. However, in practice, MCC has a very long transmission distance from the mobile device, resulting in a large latency. Mobile Edge Computing (MEC) is a technology that exists to overcome this problem. However, new problems arise from the presence of this MEC.One of the problems that arise is the selection of offloading decisions from mobile devices. Several studies consider energy efficiency / large latency or both in determining offloading decisions. However, there are not many studies that consider the movement of mobile devices in determining offloading decisions. Even though the movement of mobile devices is also very influential on latency because tasks need to be migrated to another edge server when a mobile device has moved. Several studies that have addressed this issue apply the solution to smaller, less heterogeneous simulation environments.This study used a new method of offloading decision-making that pays attention to the movement of mobile devices in a heterogeneous environment. This proposed method uses Black Widow Optimization in solving the problem of decision selection when offloading. From the simulation results, the performance of the proposed method is better than the comparison method in terms of the amount of energy consumption and delay latency.